2005
DOI: 10.1089/ast.2005.5.391
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Isolation of Hydrogen Peroxide-Resistant Spores ofBacillus pumilusfrom a Spacecraft Assembly Facility

Abstract: While the microbial diversity of a spacecraft assembly facility at the Jet Propulsion Laboratory (Pasadena, CA) was being monitored, H2O2-resistant bacterial strains were repeatedly isolated from various surface locations. H2O2 is a possible sterilant for spacecraft hardware because it is a low-temperature process and compatible with various modern-day spacecraft materials, electronics, and components. Both conventional biochemical testing and molecular analyses identified these strains as Bacillus pumilus. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
107
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 43 publications
3
107
0
1
Order By: Relevance
“…(Darby et al 2007), which requires a bacterial exopolysaccharide (Tan and Darby 2004). The contaminant was isolated and identified as a strain of the ubiquitous and important Gram-positive species B. pumilus, which has attracted detailed study as a common contaminant of spacecraft, among other reasons (Kempf et al 2005). A sample of one of the well-studied and fully sequenced strains of B. pumilus, SAFR-032, was obtained and found to lack the nematode stickiness observed in CBX120.…”
Section: Resultsmentioning
confidence: 99%
“…(Darby et al 2007), which requires a bacterial exopolysaccharide (Tan and Darby 2004). The contaminant was isolated and identified as a strain of the ubiquitous and important Gram-positive species B. pumilus, which has attracted detailed study as a common contaminant of spacecraft, among other reasons (Kempf et al 2005). A sample of one of the well-studied and fully sequenced strains of B. pumilus, SAFR-032, was obtained and found to lack the nematode stickiness observed in CBX120.…”
Section: Resultsmentioning
confidence: 99%
“…During monitoring of the microbial diversity of spacecraftassociated environments over a period of 5 years (1999)(2000)(2001)(2002)(2003)(2004), Bacillus pumilus was found to be the second most dominant species among the aerobic spore-forming bacteria (the predominant species being Bacillus licheniformis; La Duc et al, 2004a). Several of these B. pumilus isolates have exhibited elevated resistance to H 2 O 2 (Venkateswaran et al, 2001;Kempf et al, 2005) and are thus considered as 'problematic' micro-organisms, since H 2 O 2 is recommended for the bioreduction of spacecraft components.In previous studies using MALDI-TOF MS (matrix-assisted laser desorption/ionization time-of-flight mass spectrometry) Abbreviation: MALDI-TOF MS, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry.The GenBank/EMBL/DDBJ accession numbers for the 16S rRNA and gyrB gene sequences referred to in this communication are given in The bacterial strains examined in this study are shown in Table 1. A total of 13 strains of this novel micro-organism were isolated from spacecraft and assembly-facility surfaces by standard swabbing procedures (Anonymous, 1980;La Duc et al, 2004b) at various times and locations.…”
mentioning
confidence: 99%
“…During monitoring of the microbial diversity of spacecraftassociated environments over a period of 5 years (1999)(2000)(2001)(2002)(2003)(2004), Bacillus pumilus was found to be the second most dominant species among the aerobic spore-forming bacteria (the predominant species being Bacillus licheniformis; La Duc et al, 2004a). Several of these B. pumilus isolates have exhibited elevated resistance to H 2 O 2 (Venkateswaran et al, 2001;Kempf et al, 2005) and are thus considered as 'problematic' micro-organisms, since H 2 O 2 is recommended for the bioreduction of spacecraft components.…”
mentioning
confidence: 99%
“…Recently, in several microbial diversity surveys performed over a period of 3 years, 125 aerobic microbial strains were isolated from spacecraft assembly facilities (20,24,25,52,53), and their phylogenetic affiliations were determined (23, 54). Eighty-five percent of these strains were identified as gram-positive bacteria.…”
mentioning
confidence: 99%